Peran SMA Plus Yaspida Sukabumi dalam Membentuk Kepemimpinan Siswa - Ikbal Fatardo; Siti Qomariyah; Amirulloh Amirulloh; Herdi Herdi; Jenal Nurhakim (Jurnal Pendidikan dan Sastra Inggris, 2026)
This study aims to determine the role of SMA PLUS Yaspida in developing student leadership as an effort to manifest khalifatu fii al-ardi (stewards on earth) with Islamic character. The research employs a descriptive qualitative method, with data collection techniques including observation, informal interviews, and documentary studies. The results indicate that the foundational concept of SMA PLUS Yaspida is based on a national curriculum integrated with pesantren (Islamic boarding school) programs, leadership training, and the habituation of Islamic character. The primary strategy of SMA Plus YASPIDA in shaping student leadership is through the implementation of a conducive and structured student/santri organizational culture, allowing students to experience a learning by doing process in leadership imbued with Islamic values. This role is central and integrated, grounded in the concept of a Total Islamic Boarding School. Challenges encountered include time constraints, heavy academic and religious workloads, the transition from a command-based structure to student autonomy, limited perceptions of leadership, and a lack of structured, sustainable leadership training. These issues are addressed by implementing a daily responsibility delegation model and a situational leadership approach. The study concludes that the leadership program ensures students are not only academically proficient but also morally, socially, and emotionally mature as future leaders.